A review of the Taeniacanthus balistae species group (Crustacea: Copepoda: Taeniacanthidae), with descriptions of two new species - Tang, Danny; Uyeno, Daisuke; Nagasawa, Kazuya (Zootaxa, 2016)
The Taeniacanthus balistae species group is characterized by two displaced elements on an outwardly curved and elongated terminal exopodal segment of leg 4. Members of this group parasitize tetraodontiform fishes. The group is reviewed herein based on both new material collected from tetraodontiform fishes and re-examination of voucher specimens housed at the Smithsonian Institution, U.S.A. Five species are considered valid in this group, including two new species described here, Taeniacanthus dojirii sp. nov. from diodontid hosts collected from the Indo-West Pacific and Taeniacanthus ryukyuensis sp. nov. from balistid hosts collected from the Ryukyu Islands, Japan. Taeniacanthus dojirii sp. nov. differs from other members of the group by having in the female stout spines on the terminal endopodal segment of legs 2 to 4 and on the exopod of leg 5, as well as highly reduced setae on the last two exopodal segments of leg 4. Taeniacanthus ryukyuensis sp. nov. differs from other members of the group by having in the female 16–18 incomplete rows of spinules on the anal somite, minute teeth on the straight terminal claw of the maxilliped and well-developed spinulated flanges on the rami of legs 2 to 4. Supplemental morphological observations, as well as new host and locality records for Taenicanthus balistae (Claus, 1864) and Taeniacanthus similis Dojiri & Cressey, 1987, are also provided.